2014
DOI: 10.17796/jcpd.39.1.ml4h38626g66p750
|View full text |Cite
|
Sign up to set email alerts
|

Assessment for the Children's Fear Survey Schedule—Dental Subscale

Abstract: Objectives: Child dental fear causes a significant management problem. The Children's Fear Survey Schedule-Dental Subscale (CFSS-DS) is the most widely used measure of dental fear in children. This study was undertaken to develop and test reliability and validity for the Arabic version of the CFSS-DS. Study design: the English CFSS-DS was translated to Arabic language and its reliability and validity were evaluated by distributing it to 6-12 year old Arabic pediatric dental patients (n=220). Of whom 144 childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
32
2
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 31 publications
12
32
2
7
Order By: Relevance
“…There are limitations to the work presented and this is in relation to the Buridah sample (Sample 2) being all girls, the questionnaire being completed at home and that the samples were collected 2 years apart. Although much of the literature cites a difference in dental anxiety between genders, the same was not observed by El‐Housseiny et al, where they showed that the mean CFSS‐DS score for boys was 23.50 (±7.66) and for girls 23.51 (±7.83). Since no difference in mean score in CFSS‐DS existed for Saudi children, this suggested that the use of an all‐girl sample for the CFA study was acceptable.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…There are limitations to the work presented and this is in relation to the Buridah sample (Sample 2) being all girls, the questionnaire being completed at home and that the samples were collected 2 years apart. Although much of the literature cites a difference in dental anxiety between genders, the same was not observed by El‐Housseiny et al, where they showed that the mean CFSS‐DS score for boys was 23.50 (±7.66) and for girls 23.51 (±7.83). Since no difference in mean score in CFSS‐DS existed for Saudi children, this suggested that the use of an all‐girl sample for the CFA study was acceptable.…”
Section: Discussionmentioning
confidence: 85%
“…The questionnaire consisted of two parts: the first included questions about the participants’ age and gender and the second part assessed child dental anxiety using the Arabic version of the CFSS‐DS . CFSS‐DS consists of 15 questions related to various aspects of dental treatment as, for example fear of the dentist, dental treatment such as the local anaesthesia, and so forth.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A higher score reveals higher dental fear [17]. The validated Arabic version of CFSS-DS was used in this study [18]. …”
Section: Methodsmentioning
confidence: 99%